2002
DOI: 10.1139/x01-206
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in resin canal defenses in seedlings from the Sitka spruce × white spruce introgression zone

Abstract: Seedlings from 18 provenances along a coast-interior transect in the Picea sitchensis (Bong.) Carrière × Picea glauca (Moench) Voss introgression zone in northwestern British Columbia were mechanically wounded at the beginning of their third growing season to simulate natural attack by the white pine weevil, Pissodes strobi (Peck). Constitutive resin canals (CRC) in the cortex and traumatic resin canals (TRC) in the xylem of terminal shoots were characterized microscopically 4 months after wounding. Wounding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
1
36
0
2
Order By: Relevance
“…In the hybridization zone of Sitka-white spruce in north-west BC, O'Neill et al (2002) reported a strong traumatic resin formation in white spruce in response to wounding (as has been previously noted in other populations of this species (Alfaro, 1995;Tomlin et al, 1998)) compared with Sitka spruce (O'Neill et al, 2002). The most significant independent variable for predicting traumatic resin cells in trees was distance from the sea (O'Neill et al, 2002) which equates to the degree of white spruce genotypes in the hybrid mix; populations further from the sea have a greater proportion of white spruce.…”
Section: Discussionmentioning
confidence: 99%
“…In the hybridization zone of Sitka-white spruce in north-west BC, O'Neill et al (2002) reported a strong traumatic resin formation in white spruce in response to wounding (as has been previously noted in other populations of this species (Alfaro, 1995;Tomlin et al, 1998)) compared with Sitka spruce (O'Neill et al, 2002). The most significant independent variable for predicting traumatic resin cells in trees was distance from the sea (O'Neill et al, 2002) which equates to the degree of white spruce genotypes in the hybrid mix; populations further from the sea have a greater proportion of white spruce.…”
Section: Discussionmentioning
confidence: 99%
“…In P. taeda, peak resin flows appeared to be associated with moderate water deficit periods (Ruel et al, 1998;Lombardero et al, 2000). Furthermore, earlier studies on Pinaceae xylem anatomy showed that harsh environmental conditions such as high temperatures, aridity and cold winters are associated with higher frequencies and greater sizes of resin canals (Zamski, 1972;Rigling et al, 2003;Martín et al, 2010;Esteban et al, 2010), whereas an increment of annual or summer rainfall is negatively correlated with these traits (Wimmer and Grabner, 1997;O'Neill et al, 2002). Thus it is also hypothesized that constitutive and traumatic resin canal formation and de novo resin synthesis processes will be influenced by the climate characteristics of the current and the previous year.…”
Section: Introductionmentioning
confidence: 95%
“…Planting species and populations (seedlots) that are adapted to future climates preserves the host-pest balance that has been created over millennia. Provenance tests reveal that the incidence of pest attack increases sharply when populations are planted in climates that differ significantly from their origin (O'Neill et al 2002). The facilitated migration of tree species provides an opportunity to increase stand resiliency and reduce susceptibility to pests.…”
Section: Assisted Migration and Genetic Diversitymentioning
confidence: 99%